San o Evropi / Dream of Europe - Kamberović, Husnija (Pregled: časopis za društvena pitanja / Periodical for social issues, 2025)
Text is a book review Mijat Lakićević, Ljudi (i) institucije. Desimir Tošić, Latinka Perović, Vladimir Gligorov, Zoran Đinđić. Novi Sad: Akademska knjiga, 2024, 206 str.